Estimativas de parâmetros genéticos e proposição de critérios de seleção para pesos na raça Canchim - Mascioli, Arthur Dos Santos [UNESP]; De Alencar, Maurício Mello; Barbosa, Pedro Franklin; De Novaes, Antônio Pereira; Oliveira, Marcia Cristina de Sena (My University, 1996)
The objectives of this study were to obtain heritability and genetic, phenotypic and environmental correlation estimates for birth (B), weaning (WW), yearling (YW) and 18 - (EW) and 24 - month (TW) weights, and to propose selection criteria for body weight in Canchim cattle. The data were analyzed by the least-squares method with models that included the fixed effects of herd, year and month of birth, sex of calf and age of cow at calving, and the random effects of sire within herd. The heritability estimates obtained were equal to 0.36 0.06 (BW), 0.47 0.06 (WW), 0.53 0.07 (YW), 0.54 0.08 (EW) and 0.27 0.06 (TW). The genetic correlations were equal to 0.51 (BW and WW), 0.36 (BW and YW), 0.14 (BW and EW), 0.00 (BW and TW), 0.92 (WW and YW), 0.77 (WW and EW), 0.75 (WW and TW), 0.94 (YW and EW), 0.86 (YW and TW) and 0.85 (EW and TW). The phenotypic correlations ranged from 0.19 to 0.72, and the environmental correlations from 0.11 to 0.61. The results showed that, in general, mass selection for weight will result in genetic progress, selection for weight at any age will result in correlated changes at other ages, and EW and TW are good selection criteria for increasing weight in the Canchim breed.
Genetic parameters and selection criteria for body weight in Canchim cattle
Keywords: Beef cattle; Genetic correlations; Heritability; Selection